(untitled) (International Conference on Computers in Education, 2025)
This study examines the effectiveness of formative assessment integrated with educational technologies in enhancing the learning outcomes of preservice geography teachers at Can Tho University, Vietnam. A quasi-experimental design was employed over two academic years, involving 144 participants. Students were randomly assigned to an experimental group (n = 70) and a control group (n = 74). The experimental group underwent frequent formative assessments embedded in the learning process, utilizing tools such as Google Classroom, Google Forms, and Canva, with structured criteria and timely feedback. The control group primarily relied on conventional classroom practices and email-based feedback, with limited use of formative assessments. Data were collected through pre- and post-intervention surveys assessing students’ attitudes and perceptions, as well as achievement tests that combined multiple-choice and essay items. Results from paired-samples t-tests showed significant improvements in both groups, but independent-samples t-tests and ANCOVA confirmed that the experimental group demonstrated significantly greater progress (Cohen’s d = 1.30; partial η² = .365). The findings highlight that formative assessment with technology integration not only improves students’ test performance but also fosters positive changes in learning attitudes and engagement. The study contributes evidence supporting the integration of formative assessment and digital tools in teacher education to promote effective and sustainable learning.